Nitrogen Removal by a Nitritation-Anammox Bioreactor at Low Temperature - Hu, Ziye (American Society for Microbiology, 2013)
Currently, nitritation-anammox (anaerobic ammonium oxidation) bioreactors are designed to treat wastewaters with high ammonium concentrations at mesophilic temperatures (25 to 40°C). The implementation of this technology at ambient temperatures for nitrogen removal from municipal wastewater following carbon removal may lead to more-sustainable technology with energy and cost savings. However, the application of nitritation-anammox bioreactors at low temperatures (characteristic of municipal wastewaters except in tropical and subtropical regions) has not yet been explored. To this end, a laboratory-scale (5-liter) nitritation-anammox sequencing batch reactor was adapted to 12°C in 10 days and operated for more than 300 days to investigate the feasibility of nitrogen removal from synthetic pretreated municipal wastewater by the combination of aerobic ammonium-oxidizing bacteria (AOB) and anammox. The activities of both anammox and AOB were high enough to remove more than 90% of the supplied nitrogen. Multiple aspects, including the presence and activity of anammox, AOB, and aerobic nitrite oxidizers (NOB) and nitrous oxide (N(2)O) emission, were monitored to evaluate the stability of the bioreactor at 12°C. There was no nitrite accumulation throughout the operational period, indicating that anammox bacteria were active at 12°C and that AOB and anammox bacteria outcompeted NOB. Moreover, our results showed that sludge from wastewater treatment plants designed for treating high-ammonium-load wastewaters can be used as seeding sludge for wastewater treatment plants aimed at treating municipal wastewater that has a low temperature and low ammonium concentrations.